De quelques activités langagières observées lors d'un processus d'élaboration conjointe de connaissances et d'apprentissage coopératif - Thérèse Jeanneret
This article examines how multilingual French speakers give meaning to the knowledge that they must acquire in order to take an applied linguistics exam in French at the Bachelor level. The collaborative work of a group of seven students (one male and six female) is analysed on the basis of a transcription of verbal messages conducted via WhatsApp on their smartphones. Drawing on sociocultural theories of activity, this paper focuses on the participants' languaging of their knowledge. The study brings out different language activities such as the discursive development of definitions, the reasoned explanation of scientific articles, the collaborative naming of experiences related to linguistic practices, and the mobilization of learning experiences. These discursive activities about applied linguistics concepts allow for an appropriation on knowledge through what Bereiter (1994) calls progressive discourse, a discourse indicating an superior understanding of the concepts and theories in question.